ANALYSIS OF THE USE OF FAT EMULSIONS IN NEONATAL PARENTAL `NUTRITION IN UKRAINE - T.K. Znamenska; O.V. Vorobiova; L.I. Nikulina (Bukovynian State Medical University, 2020)
Fat emulsions are extremely important for newborns, especially for seriously ill, premature babies with very low and extremely low body weight (congenital or acquired pathology that causes gastrointestinal failure), if routine enteral feeding is problematic and sometimes impossible. All current updated data on the quality, efficacy and feasibility of using lipid emulsions in parenteral nutrition for medical reasons were published in the 2019 Cochrane Review "Systematic review of lipid emulsions for intravenous nutrition in term and late preterm infants". More recently, fatty emulsions obtained from several sources have become available for clinical use. SMOFLipid is one of such fat emulsion. It`s a mixture of soybean oil, medium-chain triglycerides, olive oil and fish oil in a 30: 30: 25: 15 ratio that has certain benefits. Due to the content of medium-chain triglycerides, it`s rapidly metabolized; soybean oil - a source of polyunsaturated fatty acids; olive oil - less immune effects; and fish oil - the antiinflammatory effect is enhanced, and a decrease in the frequency of bronchopulmonary dysplasia and infection in premature infants is noted. Today in Ukraine, to cover the needs for energy, calories, and essential fatty acids in term and premature babies, when oral or enteral nutrition is not possible, insufficient or contraindicated, lipid emulsion SMOFLipid is actively used as part of total parenteral nutrition. The general dynamics of prescribing lipid emulsions in Ukraine are regressive due to certain regions, where the practice of parenteral nutrition for newborns differs from other areas in sporadicity and less priority due to objective and subjective circumstances. One of the key ways to solve the problem of improving the quality of medical care for newborns in neonatal hospitals should be the introduction of a training system (seminars, practical training, etc.) for neonatologists in modern principles of conducting and international clinical guidelines for parenteral nutrition of newborns at all levels in all regions. Ukraine.